Tales of oral tradition. Essay of a generic classification - González Sanz, Carlos (Tropelías: Review of Literary Theory and Comparative Literature, 1995)
The criterion of value of truth proves to be suitable for the classification of the tales of oral tradition, on the understanding that there is always on the narrator (the real person) a clear conscience about the value of truth of the tale he is telling. According to this criterion and attending to the formal marks that each tale states, this papel' offers an example of generic classification of narrative of oral tradition presenting for each one of them one or various examples of tales recopiled in Aragón.
Keywords: Oral tradition